2022
DOI: 10.1177/21582440221099293
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Resistance Barriers to Service Robots on Alternative Attractiveness and Intention to Use

Abstract: This study examined the effect of resistance barriers on alternative attractiveness of service robots and intention to use to explain the effect of innovation resistance against such robots on customer behavior. An online survey was conducted with South Korean customers who had used hotel rooms in the past year. This study tested its hypotheses with partial least squares–structural equation modeling. The results indicate that usage barriers related to customers’ familiarity with use and tradition as well as im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 93 publications
(262 reference statements)
0
6
0
Order By: Relevance
“…Previous investigations have revealed that VB is linked to user behavior related to digitization initiatives and their resistance. Similar to other barriers, several studies have demonstrated an alliance between VB and user intentions, notably in the context of fitness apps' purchase behavior (Chakraborty et al, 2022), MOOC (Ma and Lee, 2019), mobile payment (Ghosh, 2022), and service robots (Lee and Kim, 2022). Scholars contend that VB hampers the use of products in various industries such as hotels, information technology, and banking (Khanra et al, 2020).…”
Section: Value Barriers (Vb)mentioning
confidence: 94%
See 1 more Smart Citation
“…Previous investigations have revealed that VB is linked to user behavior related to digitization initiatives and their resistance. Similar to other barriers, several studies have demonstrated an alliance between VB and user intentions, notably in the context of fitness apps' purchase behavior (Chakraborty et al, 2022), MOOC (Ma and Lee, 2019), mobile payment (Ghosh, 2022), and service robots (Lee and Kim, 2022). Scholars contend that VB hampers the use of products in various industries such as hotels, information technology, and banking (Khanra et al, 2020).…”
Section: Value Barriers (Vb)mentioning
confidence: 94%
“…This has occurred because of changes affecting existing societal norms and consumer values associated with adopting new technology (Ram and Sheth, 1989). As part of the psychological barrier, there is the traditional barrier, it would be impossible for any new product to be accepted by consumers, whose current certainty systems would skirmish with new technology (Lee and Kim, 2022). As such, consumers' psychological states determine traditional barriers and the fact that smart technology has a "short shelf life " and "low satisfaction" (Sadiq et al, 2021), in contrast to traditional technology.…”
Section: Traditional Barriers (Tb)mentioning
confidence: 99%
“…Accordingly, the authors emphasized that FLEs and FLSRs should collaborate to reduce customer concerns. FLSR implementation in the tourism industry changes the overall service experience for customers [34,50]. Since customers are habituated to FLE services, they perceive the FLSR service process as inconvenient and complex [34].…”
Section: The Importance Of Employee-flsr Collaboration In the Tourism...mentioning
confidence: 99%
“…FLSR implementation in the tourism industry changes the overall service experience for customers [34,50]. Since customers are habituated to FLE services, they perceive the FLSR service process as inconvenient and complex [34]. This creates a psychological barrier to change for customers, which requires FLE-FLSR collaboration in the service workplace to mitigate customer concerns [34].…”
Section: The Importance Of Employee-flsr Collaboration In the Tourism...mentioning
confidence: 99%
See 1 more Smart Citation